Development of solar and gas hybrid energy bed dryer with implementing multivariable expert system controls. Issue 1 (April 2020) - Putra, B; Waris, A; Iqbal,
Abstract: This study aims to develop a bed dryer prototype with optimum use of energy sources (solar and Liquified Petroleum Gas (LPG) hybrid). The material used in this study was fresh cocoa beans (Sulawesi 2 clones) purchased directly from Pattalassang Village, Tompobulu Subdistrict, Bantaeng Regency. The energy sources used were solar energy panels combined with an LPG burner. The tests conducted consisted of: a) control system test, b) drying test, and c) energy consumption test. In the drying test, the setting point was 60°C and two methods of energy supply were (1) Solar and LPG hybrid energy, (2) LPG energy only. The test results show that the control system works well, and the flame of the burner can be set automatically at low, medium, and high along with the temperature in the drying chamber and the collector. The temperature of the dryer was very stable, and no overshoot, The settling time is quite short, which is only 5 minutes. Hybrid furnace operation was more efficient (gas usage was about 64.8% compared to non-hybrid). Hybrid furnace operation consumed only 0.116 kg/hour of gas while non-hybrid operation consumed LPG of about 0.179 kg/hour.